2019
DOI: 10.7150/thno.29579
|View full text |Cite
|
Sign up to set email alerts
|

miR-26a Limits Muscle Wasting and Cardiac Fibrosis through Exosome-Mediated microRNA Transfer in Chronic Kidney Disease

Abstract: Uremic cardiomyopathy and muscle atrophy are associated with insulin resistance and contribute to chronic kidney disease (CKD)-induced morbidity and mortality. We hypothesized that restoration of miR-26a levels would enhance exosome-mediated microRNA transfer to improve muscle wasting and cardiomyopathy that occur in CKD. Methods: Using next generation sequencing and qPCR, we found that CKD mice had a decreased level of miR-26a in heart and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
107
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 121 publications
(122 citation statements)
references
References 50 publications
8
107
0
Order By: Relevance
“…At present, intraperitoneal injection, intravenous injection, and local application are the main methods by which EXOs are applied in vivo [ 67 69 ]. Muscle injection is primarily used for the treatment and study of skeletal muscle atrophy [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…At present, intraperitoneal injection, intravenous injection, and local application are the main methods by which EXOs are applied in vivo [ 67 69 ]. Muscle injection is primarily used for the treatment and study of skeletal muscle atrophy [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Wang has ascertained the treatment for exosomes (containing Lamp2b)/miR-26a elevated cross-sectional areas of skeletal muscles, diminished the upregulation of FOXO32/atrogin-1, and TRIM63/MuRF1 and depressed cardiac brosis lesions. [23] Moreover, exosomes as a kind of extracellular vesicle have emerged as a promising therapeutic delivery platform due to their speci c composition and biological properties, providing the nervous system with effective agents for treating various diseases. [24] A recent study has reported that exosomes from serum-deprived mesenchymal stem cells were utilized to deliver siRNAs to neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Given to these properties, they are recognized as promising biomarkers for diagnosis and prognosis of many diseases ( Gurunathan et al., 2019 ). There is growing evidence that exosomes have therapeutic effects on the renal diseases, such as acute tubular injury ( Pan et al., 2019 ) and chronic kidney disease (CKD) ( Wang B. et al., 2019 ). Furthermore, it has been indicated that exosomes can improve renal ischemic-reperfusion injury (IRI)-induced renal structural injury by restraining nuclear factor-κB (NF-κB) activation to subside the expressions of inflammatory cytokines ( Li L. et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%